Light ultrathin PEO-based solid electrolyte with high ion transfer number and preparation method thereof
Through electrospinning technology, the PAN support layer covering UIO-66 nanoparticles is combined with a high salt concentration PEO electrolyte, which solves the problem of slow Na+ diffusion in PEO-based solid electrolytes, and achieves the improvement of high ion transfer number and mechanical properties, improving The cycle stability and energy density of sodium metal batteries are obtained.
Patent Information
- Application Number
- CN202411659534.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The slow diffusion of Na+ in PEO-based solid electrolytes leads to low ion conductivity and ion transfer numbers at room temperature, resulting in uneven deposition of electrolyte/electrode interfaces, easy growth of dendrites, causing sodium metal batteries to fail, and existing methods will improve conductivity. Damage mechanical properties.
Electrospinning technology is used to combine PAN-coated UIO-66 nanoparticles with high salt concentration PEO solid electrolyte as a support layer. UIO-66 nanoparticles are prepared by hydrothermal method, and high salt concentration is coated on the PAN support layer. The PEO-based solid electrolyte slurry is then heat-pressed to form a lightweight and ultra-thin PEO-based solid electrolyte.
It achieves high ion transfer number and excellent mechanical properties, promotes uniform deposition of Na+ on the negative electrode surface, improves sodium ion transfer number and battery cycling stability and rate performance, and enhances the battery's energy density.
Smart Images

Figure CN119162842A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolyte materials for sodium metal batteries, and particularly relates to a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number and a preparation method thereof. Background Art
[0002] With the vigorous development of new energy technologies, lithium batteries have been used in all aspects of production and life, but due to the limited reserves of lithium elements worldwide, my country's lithium resources are not abundant. The reserves of sodium elements in sodium batteries are much greater than those of lithium elements, and the reserves are abundant, and the mining and production costs are relatively low (down about 40%), which is considered to be an attractive next-generation energy storage device.
[0003] In order to obtain high energy density, the voltage difference between the positive and negative electrodes needs to be large enough, and sodium metal has a low reduction potential (-2.71 V) and a high theoretical capacity (1166 mAh g -1 ), based on this, using sodium metal as the battery negative electrode can effectively cope with the shortage of lithium resources and is an important method to achieve high energy density.
[0004] However, sodium metal batteries also face thorny challenges. In traditional liquid electrolyte systems, the metallic sodium negative electrode will react directly with the liquid electrolyte, resulting in poor battery cycle performance and even serious safety problems due to electrolyte leakage and combustion.
[0005] Based on this, people have developed a variety of solid electrolyte strategies to replace electrolytes and diaphragms to avoid the flammability and leakage problems of liquid batteries. Solid electrolytes replace the original electrolytes and diaphragms, effectively protecting the sodium metal negative electrode. At the same time, solid electrolytes can effectively achieve high energy density of batteries and improve cycle stability. Among the various types of solid electrolytes, polymer solid electrolytes are the first choice, and PEO-based solid electrolytes have excellent Na + Solventizing ability, low cost, and good roll-to-roll processing performance are considered to have great development potential.
[0006] However, in PEO-based solid electrolytes, due to the + The slow diffusion of ions leads to a low ionic conductivity (10 -7 -10 -8 ) and ion transfer number (<0.2), resulting in uneven electrolyte / electrode interface deposition, easy growth of dendrites and battery failure. Although adding ionic liquids or plasticizers can improve conductivity, it will cause mechanical properties to deteriorate and have an adverse effect on the cycle. Adding various inorganic fillers can also effectively promote Na + However, the fillers are prone to agglomeration and the improvement of electrochemical performance is limited.
[0007] To this end, this paper proposes a lightweight and ultra-thin PEO-based solid electrolyte with a high ion transfer number and a preparation method, which has an ultra-thin thickness and a high ion transfer number, which is conducive to achieving a high energy density of sodium metal batteries. Summary of the invention
[0008] The purpose of the present invention is to provide a lightweight and ultra-thin PEO-based solid electrolyte with a high ion transfer number and a preparation method. PAN-coated UIO-66 nanoparticles are used as a support layer and composited with a PEO solid electrolyte with a high salt concentration by using electrospinning technology to achieve a lightweight and ultra-thin PEO-based solid electrolyte with a high ion transfer number.
[0009] To achieve the above object, the present invention provides a method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number, comprising the following steps: S1. Preparation of UIO-66 nanoparticles by hydrothermal method; S2, preparation of UIO-66@PAN support layer by electrospinning technology; S3, mixing a certain ratio of PEO and sodium bis(trifluoromethylsulfonyl)imide in acetonitrile to obtain a PEO-based solid electrolyte slurry with a high salt concentration; S4, coating a high salt concentration PEO-based solid electrolyte slurry on the PAN support layer and drying it to obtain a PAN / PEO membrane; S5. Hot-pressing the dried PAN / PEO film to obtain a PEO-based solid electrolyte.
[0010] Preferably, the step 1 specifically comprises the following steps: S1-1, dissolving ZrCl4 in N,N-dimethylformamide and ultrasonicating for 30 minutes, adding BDC, concentrated hydrochloric acid and benzoic acid to the above solution to obtain UIO-66 nanoparticles; S1-2, adding a certain amount of deionized water to adjust the size of UIO-66 nanoparticles; S1-3, after ultrasonic treatment of the solution obtained in S1-2 for 15 minutes, transfer it to a 200 mL hydrothermal kettle and heat it in an oven at 120°C for 24 hours; S1-4. After cooling to room temperature, the crude product was collected by centrifugation and washed with methanol at least three times; the washed product was activated in a vacuum drying oven at 150° C. for 24 hours to obtain the final product, UIO-66 nanoparticles.
[0011] Preferably, in step S1-1, the molar volume ratio of ZrCl4 to N,N-dimethylformamide is 1 mol:18L, and the molar volume ratio of BDC, concentrated hydrochloric acid and benzoic acid to N,N-dimethylformamide is 1 mol:2 mol:20 mol:18L.
[0012] Preferably, the step 2 specifically comprises the following steps: S2-1, PAN powder and UIO-66 nanoparticles were dried at 80 °C in a vacuum environment for 24 h; S2-2, weigh 0.5 g of dried PAN powder and UIO-66 nanoparticles respectively and dissolve them in N, N-dimethylformamide to prepare a mixed solution with a mass fraction of 10%; S2-3, stirring the mixed solution for 3 h at room temperature and then completely dissolving it to obtain an electrospinning precursor solution; S2-4, spinning PAN@UIO-66 membrane with uniform fiber size by controlling electrospinning process parameters; S2-5. The prepared PAN@UIO-66 film was vacuum dried in a vacuum oven at 120 °C for 24 h to remove residual solvent and moisture.
[0013] Preferably, the electrospinning process parameters in step S2-4 are: high voltage 12 KV, low voltage -1 KV, nozzle flow rate 0.08 mm / min, receiver rotation speed 600 r / min, nozzle and receiver distance 15 cm, translation distance 25 cm.
[0014] Preferably, in step S3, the ratio of PEO and sodium bis(trifluoromethylsulfonyl)imide is [EO / Na + ]=6:1 ratio, and the stirring time is 12 hours.
[0015] Preferably, in step S4, the thickness of the PAN support film is 15-20 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm.
[0016] Preferably, the drying process in step S4 is to first place it at room temperature for 6 hours, and then place it in a vacuum oven at 80° C. for drying for 12-24 hours.
[0017] Preferably, in step S5, the hot pressing pressure is 40 MPa, the hot pressing temperature is 70° C., and the hot pressing time is 15-30 min.
[0018] The present invention also provides a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number, which is prepared by adopting the preparation method of the lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number.
[0019] Therefore, the present invention adopts the above-mentioned lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number and a preparation method, and its beneficial effects are: 1. High concentrations of bis(trifluoromethanesulfonyl)imide (TFSI-) salts can generate ion clusters, providing additional Na+ transport pathway to promote Na + transport; 2. The pore size of UIO-66 (8.1Å) is slightly larger than that of TFSI- (7.9Å), where TFSI- can adsorb UIO-66 particles to inhibit their movement, resulting in a high Na+ transfer number of 0.80. + The number of transfers makes Na + Uniform deposition on the negative electrode surface; 3. UIO-66 particles are tightly packed in 3D PAN nanowires, providing a high mechanical strength of 3.46 MPa at a thickness of 25 μm. + The transfer number provides a continuous ion conduction pathway; 4. Metal-organic framework UIO-66 particles with suitable particle size and appropriate pore size are applied to solid polymer electrolytes. UIO-66 particles can capture anions, thereby releasing more freely conductive sodium ions. On the other hand, PEO electrolytes with high salt concentrations can generate ion clusters and effectively provide ion transport pathways. The two work synergistically to increase the sodium ion transfer number. At the same time, in order to increase the energy density of the battery, an oxidation-resistant PAN electrospinning membrane is used as a rigid skeleton to prepare a lightweight, ultra-thin PEO-based solid electrolyte with a high ion transfer number.
[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 TEM image of Example 1 of the present invention; Figure 2 It is the SEM image of Example 1 of the present invention; Figure 3 It is the SEM image of Example 1 of the present invention; Figure 4 It is a comparison diagram of stress-strain curves of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention; Figure 5 This is a comparison chart of the ionic conductivity of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention; Figure 6 It is a comparison diagram of the critical current density of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 7 A graph showing a change in the sodium ion migration number of a PEO-based solid electrolyte prepared in Example 1 of the present invention; Figure 8This is a graph showing the change in sodium ion migration number of the PEO-based solid electrolyte prepared in Comparative Example 1; Fig. 9 It is a comparison diagram of the cycle curves of the PEO-based solid electrolyte prepared in Example 1 of the present invention and Comparative Example 2; Fig.10 It is a comparison chart of the cycle curves of the PEO-based solid electrolyte prepared in Example 1 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0023] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0024] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0025] The present invention is further described below with reference to the accompanying drawings and specific embodiments.
[0026] The present invention provides a method for preparing a lightweight, ultra-thin, high ion transfer number PEO-based solid electrolyte, which is achieved by the following steps: Step S1, preparing UIO-66 nanoparticles by hydrothermal method; Step S1 specifically includes the following steps: Step 1-1, ZrCl4 (0.932 g, 4.0 mmol) was dissolved in N,N-dimethylformamide (DMF, 72 mL) and ultrasonicated for 30 minutes. Then, BDC (0.660 g, 4 mmol), concentrated hydrochloric acid (0.670 ml, 8.0 mmol) and benzoic acid (9.660 g, 80.0 mmol) were added to the above solution.
[0027] Step 1-2: Add a certain amount of deionized water to adjust the size of the UIO-66 nanoparticles to obtain a suitable particle size.
[0028] Step 1-3: After ultrasonic treatment for 15 minutes, the mixed solution was transferred to a 200 mL hydrothermal kettle and heated in an oven at 120° C. for 24 hours.
[0029] Step 1-4: After cooling to room temperature, the crude product was collected by centrifugation and washed with methanol for more than three times to remove the remaining reactants. Finally, the pure phase was activated in a vacuum drying oven at 150°C for 24 hours to remove the trace amount of solvent remaining in the pores to obtain the final product UIO-66.
[0030] Step S2, preparing a UIO-66@PAN support layer by electrospinning technology; Step S2 specifically includes the following steps: Step S2-1, drying the PAN powder and UIO-66 nanoparticles at 80 °C in a vacuum environment for 24 h; Step S2-2, weighing 0.5 g of the dried PAN powder and UIO-66 nanoparticles and dissolving them in N,N-dimethylformamide to prepare a solution with a mass fraction of 10%; Step S2-3, stirring at room temperature for 3 h and then completely dissolving to obtain an electrospinning precursor solution; Step S2-4, spinning a PAN@UIO-66 membrane with uniform fiber size by controlling electrospinning process parameters; Step S2-5: drying the prepared PAN film in a vacuum oven at 120° C. for 24 h to remove residual solvent and water.
[0031] The electrospinning process parameters in step S2-4 are: high voltage 12 KV, low voltage -1 KV, nozzle flow rate 0.08 mm / min, receiver rotation speed 600 r / min, nozzle and receiver distance 15 cm, translation distance 25 cm.
[0032] Step S3, mixing and stirring PEO and NaTFSI in a certain ratio in acetonitrile to obtain a slurry of a PEO-based solid electrolyte with a high salt concentration; The ratio of PEO to NaTFSI in step S3 is [EO / Na + ]=6:1, stirring time is 12 hours.
[0033] Step S4, coating a high salt concentration PEO-based solid electrolyte slurry on the PAN support layer and drying it to obtain a PAN / PEO membrane; In step 4, the thickness of the PAN support film is 15-20 μm, and the coating scale of the slurry of the PEO-based solid electrolyte is 150-250 μm.
[0034] The drying process in step 4 is to place it at room temperature for 6 hours, and then place it in a vacuum oven and dry it at 80° C. for 12-24 hours.
[0035] Step S5: hot-pressing the dried PAN / PEO film to obtain a PEO-based solid electrolyte.
[0036] In step S5, the hot pressing pressure is 40 MPa, the hot pressing temperature is 70° C., and the hot pressing time is 15-30 min.
[0037] The following examples and comparative examples are provided for further explanation: Example 1 discloses the following preparation method: Step 1. ZrCl4 (0.932 g, 4.0 mmol) was dissolved in N, N-dimethylformamide (DMF, 72 mL) and ultrasonicated for 30 min. Then, BDC (0.660 g, 4 mmol), concentrated hydrochloric acid (0.670 mL, 8.0 mmol) and benzoic acid (9.660 g, 80.0 mmol) were added to the above solution, and then a certain amount of deionized water was added to adjust the size of UIO-66 nanoparticles to obtain a suitable particle size. After ultrasonic treatment for 15 min, the mixed solution was transferred to a 200 mL hydrothermal kettle and heated in an oven at 120 ° C for 24 h. After cooling to room temperature, the crude product was collected by centrifugation and washed with methanol for more than three times to remove the remaining reactants. Finally, the pure phase was activated in a vacuum drying oven at 150 ° C for 24 h to remove the trace solvent remaining in the pores to obtain the final product UIO-66.
[0038] Step 2: Dry the PAN powder and UIO-66 nanoparticles in a vacuum environment at 80 °C for 24 h; weigh 0.5 g of the dried PAN powder and UIO-66 nanoparticles and dissolve them in N,N-dimethylformamide to prepare a 10% solution by mass, stir at room temperature for 3 h until completely dissolved, and obtain an electrospinning precursor solution. By controlling the electrospinning process parameters (high voltage 12 KV, low voltage -1 KV, nozzle flow rate 0.08 mm / min, receiver speed 600 r / min, nozzle and receiver distance 15 cm, translation distance 25 cm), a PAN@UIO-66 film with uniform fiber size was spun; then the prepared PAN film was vacuum dried in a vacuum oven at 120 °C for 24 h to remove residual solvent and moisture; Step 3, 500 mg of PEO and 600 mg of NaTFSI were mixed and stirred in 10 ml of acetonitrile to obtain a slurry of a PEO-based solid electrolyte with a high salt concentration; the stirring time was 12 hours; Step 4: coating the high-salt concentration PEO-based solid electrolyte slurry on the PAN support layer by a coating machine and drying to obtain a PAN / PEO film; the thickness of the PAN support film is 15-20 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is first placed at room temperature for 6 hours, and then placed in a vacuum oven and dried at 80° C. for 12-24 hours; Step 5: hot-press the dried PAN / PEO film to obtain a PEO-based solid electrolyte; the hot-pressing pressure is 40 MPa, the hot-pressing temperature is 70° C., and the hot-pressing time is 15-30 min, to obtain the PEO-based solid electrolyte sample of Example 1.
[0039] Comparative Example 1 Step 1, 500 mg PEO and 230 mg NaTFSI were mixed and stirred in acetonitrile to obtain a slurry of a PEO-based solid electrolyte; the stirring time was 12 hours; Step 2: pour the obtained PEO-based solid electrolyte slurry onto a polytetrafluoroethylene mold, dry it at room temperature for 12 hours, and dry it at 60 degrees in vacuum for 12 hours; and obtain the PEO-based solid electrolyte sample of Comparative Example 1.
[0040] Comparative Example 2 Step 1. Dry the PAN powder in a vacuum environment at 80 °C for 24 h; weigh 0.5g of the dried PAN powder and dissolve it in N,N-dimethylformamide to prepare a 10% solution by mass. Stir it at room temperature for 3 h until it is completely dissolved to obtain an electrospinning precursor solution. By controlling the electrospinning process parameters (high voltage 12 KV, low voltage -1 KV, nozzle flow rate 0.08 mm / min, receiver speed 600 r / min, nozzle and receiver distance 15 cm, translation distance 25 cm.), a PAN film with uniform fiber size was spun; then the prepared PAN film was vacuum dried in a vacuum oven at 120 °C for 24 h to remove residual solvent and moisture; Step 2: 500 mg of PEO and 600 mg of NaTFSI were mixed and stirred in 10 ml of acetonitrile to obtain a slurry of a PEO-based solid electrolyte with a high salt concentration; the stirring time was 12 hours; Step 3, coating the high salt concentration PEO-based solid electrolyte slurry on the PAN support layer by a coating machine and drying to obtain a PAN / PEO film; the thickness of the PAN support film is 15-20 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is first placed at room temperature for 6 hours, and then placed in a vacuum oven and dried at 80°C for 12-24 hours; Step 4: hot-press the dried PEO-based solid electrolyte; the hot-pressing pressure is 40 MPa, the hot-pressing temperature is 70° C., and the hot-pressing time is 15-30 min, to obtain the PEO-based solid electrolyte sample of Comparative Example 2.
[0041] This sample was labeled HC-PEO.
[0042] The three samples prepared in the above examples and comparative examples were characterized in terms of morphology and performance, and the results are as follows: 1. Transmission electron microscopy (TEM) characterization The UIO-66 nanoparticles prepared in Example 1 of the present invention were characterized by TEM. Figure 1 This is the TEM image of Example 1 of the present invention; it can be seen that the Zr element of the prepared UIO-66 particles is evenly distributed.
[0043] 2. Scanning electron microscopy (SEM) characterization Figure 2 This is a SEM image of the UIO-66@PAN structure prepared by electrospinning in Example 1 of the present invention. It can be seen that UIO-66 is closely arranged in the PAN nanowires. Figure 3 This is a SEM cross-sectional view of the PEO-based solid electrolyte prepared in Example 1 of the present invention. It can be seen that the thickness of the prepared PEO-based solid electrolyte is about 25 μm.
[0044] 3. Mechanical properties test Figure 4 : is a stress-strain curve comparison diagram of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The PEO-based solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention were subjected to stress-strain tests. The results are as follows: Figure 4 As shown, it can be observed that the mechanical properties of the PEO-based solid electrolyte prepared in Example 1 are significantly higher than those of the samples prepared in Comparative Example 1 and Comparative Example 2.
[0045] 4. Ionic conductivity test (EIS) Figure 5 : is a comparison chart of the ionic conductivity of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention were tested for ionic conductivity. The results are as follows: Figure 5 As shown, it can be observed that the PEO-based solid electrolyte sample prepared in Example 1 has a higher ionic conductivity.
[0046] 5. Critical current density (CCD) test Figure 6: is a comparison chart of the critical current density of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The critical current density of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention was tested. The results are as follows: Figure 6 As shown, it can be observed that the PEO-based solid electrolyte sample prepared in Example 1 has a higher critical current density and a lower overpotential than those of Comparative Example 1 and Comparative Example 2, and the comprehensive performance of Example 1 is the best; 6. Sodium ion migration number test (it) Figure 7 A graph showing a change in the sodium ion migration number of a PEO-based solid electrolyte sample prepared in Example 1 of the present invention; Figure 8 The sodium ion migration number change diagram of the PEO-based solid electrolyte sample prepared in Comparative Example 1 of the present invention is shown in Figure 1. The lithium ion migration number test is performed on the PEO-based solid electrolyte sample prepared in Example 1 of the present invention. The results are as follows: Figure 7 As shown; the high salt concentration PEO-based solid electrolyte sample obtained in Comparative Example 1 was tested for ion migration number, and the results are as follows Figure 8 As shown; it can be observed that the PEO-based solid electrolyte prepared in Example 1 has a higher lithium ion transference number (0.80).
[0047] 7. Electrochemical performance test Fig. 9 This is a comparison chart of the cycle curves of the PEO-based solid electrolyte samples prepared in Example 1 and Comparative Example 2 of the present invention; Fig.10 The figure is a comparison chart of the rate performance of the PEO-based solid electrolyte samples prepared in Example 1 of the present invention and Comparative Example 2. The PEO-based solid electrolytes prepared in Example 1 of the present invention and Comparative Example 2 are assembled into button batteries with Na3V2(PO4)3 positive electrode and sodium metal negative electrode, respectively. The electrochemical performance of the two button batteries is tested. The results are as follows: Fig. 9 , 10 As shown, the PEO-based solid electrolyte sample prepared in Example 1 has better cycle performance and rate performance.
[0048] It can be seen from Example 1 and Comparative Examples 1 and 2 that the UIO-66@PAN structure prepared by the present invention can adsorb anions through the appropriate pore size of UIO-66, promote Na + The lightweight, ultra-thin, high ion transfer number PEO-based solid electrolyte prepared with this as filler has a thickness of about 25μm, has better mechanical properties, ion conductivity, ion transfer number and critical current density, and the assembled battery has better cycle performance and rate performance. Combining the above advantages, this electrolyte membrane is conducive to achieving high energy density of all-solid-state sodium metal batteries.
[0049] Therefore, the present invention proposes a lightweight and ultra-thin PEO-based solid electrolyte with a high ion transfer number and a preparation method, and utilizes electrospinning technology to composite PAN-coated UIO-66 nanoparticles as a support layer with a PEO solid electrolyte with a high salt concentration, thereby achieving a lightweight and ultra-thin PEO-based solid electrolyte with a high ion transfer number.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number, characterized in that: The following steps are involved: S1. Preparation of UIO-66 nanoparticles by hydrothermal method; S2, preparation of UIO-66@PAN support layer by electrospinning technology; S3, mixing a certain ratio of PEO and sodium bis(trifluoromethylsulfonyl)imide in acetonitrile to obtain a PEO-based solid electrolyte slurry with a high salt concentration; S4, coating a high salt concentration PEO-based solid electrolyte slurry on a PAN support layer and drying the slurry to obtain a PAN / PEO membrane; S5. Hot-pressing the dried PAN / PEO film to obtain a PEO-based solid electrolyte.
2. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: The step 1 specifically comprises the following steps: S1-1, dissolving ZrCl4 in N,N-dimethylformamide and ultrasonicating for 30 minutes, adding BDC, concentrated hydrochloric acid and benzoic acid to the above solution to obtain UIO-66 nanoparticles; S1-2, adding a certain amount of deionized water to adjust the size of UIO-66 nanoparticles; S1-3, after ultrasonic treatment of the solution obtained in S1-2 for 15 minutes, transfer it to a 200 mL hydrothermal kettle and heat it in an oven at 120°C for 24 hours; S1-4. After cooling to room temperature, the crude product was collected by centrifugation and washed with methanol at least three times; the washed product was activated in a vacuum drying oven at 150° C. for 24 hours to obtain the final product, UIO-66 nanoparticles.
3. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 2, characterized in that: In step S1-1, the molar volume ratio of ZrCl4 to N,N-dimethylformamide is 1 mol:18L, and the molar volume ratio of BDC, concentrated hydrochloric acid and benzoic acid to N,N-dimethylformamide is 1 mol:2 mol:20 mol:18L.
4. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: The step 2 specifically includes the following steps: S2-1, PAN powder and UIO-66 nanoparticles were dried at 80 °C in a vacuum environment for 24 h; S2-2, weigh 0.5 g of dried PAN powder and UIO-66 nanoparticles respectively and dissolve them in N, N-dimethylformamide to prepare a mixed solution with a mass fraction of 10%; S2-3, stirring the mixed solution for 3 h at room temperature and then completely dissolving it to obtain an electrospinning precursor solution; S2-4, spinning PAN@UIO-66 membrane with uniform fiber size by controlling electrospinning process parameters; S2-5. The prepared PAN@UIO-66 film was vacuum dried in a vacuum oven at 120 °C for 24 h to remove residual solvent and moisture.
5. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 4, characterized in that: The electrospinning process parameters in step S2-4 are: high voltage 12 KV, low voltage -1 KV, nozzle flow rate 0.08 mm / min, receiver rotation speed 600 r / min, nozzle and receiver distance 15 cm, translation distance 25 cm.
6. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: In step S3, the ratio of PEO and sodium bis(trifluoromethylsulfonyl)imide is [EO / Na + ]=6:1 ratio, and the stirring time is 12 hours.
7. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: In the step S4, the thickness of the PAN support film is 15-20 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm.
8. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: The drying process in step S4 is to place the mixture at room temperature for 6 hours and then place the mixture in a vacuum oven at 80° C. for 12-24 hours.
9. The method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number according to claim 1, characterized in that: In step S5, the hot pressing pressure is 40 MPa, the hot pressing temperature is 70° C., and the hot pressing time is 15-30 min.
10. A lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number, characterized in that: The solid electrolyte is prepared by the method for preparing a lightweight ultra-thin PEO-based solid electrolyte with a high ion transfer number as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Inorganic-organic nano composite solid electrolyte membrane and preparation method and application thereof
CN109638349A
Preparation method of polymer electrolyte composite membrane for solid-state battery
CN110911742A
Preparation method of thermally-stable, ultrathin, light and flame-retardant PEO-based solid electrolyte
CN115332624A
Multi-layer composite electrolyte membrane based on metal-organic framework material and preparation method of multi-layer composite electrolyte membrane
CN115458807A
Novel self-supporting metal organic framework-carbon nanotube composite capacitive deionized membrane and preparation method thereof
CN116099395A
Cited By
Modified pEO-based solid-state electrolyte and preparation method and application thereof
CN122992166A
